The spider genera Azerithonica and Tegenaria (Aranei: Agelenidae: Tegenariini) in Iran - Alireza Zamani; Yuri M. Marusik (KMK Scientific Press, 2022)
Two Tegenariini genera occurring in Iran, Azerithonica Guseinov, Marusik et Koponen, 2005 and Tegenaria Latreille, 1804 are revised. As a result, the former genus and its type species, Azerithonica hyrcanica Guseinov, Marusik et Koponen, 2005 are recorded in Iran for the first time. A new species, A. sagartia sp.n. (♀, Mazandaran) is described from northern Iran, representing the second species of Azerithonica, enabling us to provide an updated diagnosis for the genus. Furthermore, six new species of Tegenaria are described from western and northern Iran, namely: T. arsacia sp.n. (♀, Hamedan), T. daylamanica sp.n. (♀, Gilan), T. eros sp.n. (♀, Golestan), T. guseinovi sp.n. (♀, Kermanshah), T. rahnamayi sp.n. (♀, Mazandaran) and T. shirin sp.n. (♂, Kermanshah). In addition, T. halidi Guseinov, Marusik et Koponen, 2005, previously known from Azerbaijan only, is newly recorded for the fauna of Iran, and new distribution records are provided for T. domestica (Clerck, 1757), T. lenkoranica Guseinov, Marusik et Koponen, 2005 and T. pagana C.L. Koch, 1840. With the exception of the widely-distributed and well-known T. domestica and T. pagana, all of the remaining species are illustrated, and known distributions of Azerithonica spp. and all Iranian Tegenaria spp. are mapped.